The Role of Ideal Affect in the Experience and Memory of Emotions - SCOLLON, Christie N. (Institutional Knowledge at Singapore Management University, 2009)
According to Affect Valuation Theory (Tsai et al. Journal of Personality and Social Psychology, 54, 1031-1039), culture influences how people want to feel (ideal affect). Integrating Affect Valuation Theory with the Time-sequential Framework of Subjective Well-being (KIM-Prieto et al. Journal of Happiness Studies, 6, 261-300), we proposed that cultural norms influence the memory, but not the experience, of emotion. The present study examined the role of ideal affect in relation to experience sampling and retrospective reports of emotion. Ideal affect correlated with retrospective reports but not experience sampling reports. Extraversion and neuroticism were more strongly related to experience sampling reports than to ideal levels of emotion. Results suggest that retrospective reports of emotion involve a dynamic process that incorporates cultural information into the reconstruction whereas on-line emotions are more constrained by temperament.